2007
DOI: 10.1086/511636
|View full text |Cite
|
Sign up to set email alerts
|

Revaccination of Children after Completion of Standard Chemotherapy for Acute Leukemia

Abstract: Revaccination of children after standard chemotherapy is important, and protection can be achieved in the majority of these children using a simple schedule of 1 vaccine dose at 6 months after completion of leukemia therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
96
2
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 39 publications
(49 reference statements)
6
96
2
3
Order By: Relevance
“…We agree with the recommendation of many others that ALL patients should be re-vaccinated following completion of chemotherapy [3,6,21,24]. Only Fioredda et al [23] considered administration of another complete vaccination schedule to each ALL subject over treatment taking into account the economical aspect of vaccines and laboratory kits.…”
Section: Post-chemotherapy Vaccination Recommendations For Allsupporting
confidence: 60%
See 3 more Smart Citations
“…We agree with the recommendation of many others that ALL patients should be re-vaccinated following completion of chemotherapy [3,6,21,24]. Only Fioredda et al [23] considered administration of another complete vaccination schedule to each ALL subject over treatment taking into account the economical aspect of vaccines and laboratory kits.…”
Section: Post-chemotherapy Vaccination Recommendations For Allsupporting
confidence: 60%
“…In Nilsson et al's [6] study 14 ALL patients without immunity against measles were re-vaccinated after chemotherapy and only 8 patients (57%) responded. Patel et al [21] reported higher re-vaccination responses (94%) in patients with ALL and AML.…”
Section: Post-chemotherapy Vaccination Recommendations For Allmentioning
confidence: 98%
See 2 more Smart Citations
“…With reference to vaccine response, Patel et al reported antibody response to MMR vaccine in more than 94% of children who had completed standard chemotherapy for acute leukemia, without adverse reactions. 72 …”
Section: Live Attenuated Vaccinesmentioning
confidence: 99%